Preoperative Parental Anxiety and Concerns: A Prospective Observational Study - Ram, Rajesh; Dubey, Prakash K; Singh, Swati; Kumar, Akhileshwar (Journal of the Portuguese Society of Anesthesiology, 2025)
Introduction: Current understanding of risk factors associated with parental anxiety focuses on socio-demographic and situational factors, yielding inconsistent results across different populations. Seasonality influences mood and anxiety in the general population through mechanisms like sunlight exposure (vitamin D synthesis, circadian rhythm regulation) and weather-imposed social isolation. Thus, this study was conducted to assess various factors associated with parental anxiety in order to improve the perioperative experience and outcomes for children and their parents. Methods: Five hundred parents were included in the study, and the level of anxiety, need for information were assessed with the Amsterdam Preoperative Anxiety and Information Scale (modified by including questions in the local language) at time points: evening before surgery (T1); the preoperative holding area (T2), and after the child was transferred inside operation room (T3). The primary outcome of this study was to determine the changes in anxiety level and need for information about anesthesia and surgery among the parents at three different time points preoperatively. The secondary outcomes included analyzing the variables that can affect anxiety: gender, level of education, area of residence, access to internet and season of surgery. Parametric tests were used for significance, and repeated-measure analysis of variance was performed. Results: Parents displayed higher levels of anxiety related to surgery compared to anesthesia. There was no effect of gender, education, area of residence, and Internet access on total anxiety score. Weather conditions are an important factor that can influence parental anxiety before surgery. Parents exhibited higher anesthesia-related and surgical anxiety levels during the summer season. Conclusion: Apart from multiple well-documented factors, less studied factors like change in seasons may influence parental anxiety thus enabling ...